Pengaruh Kepemimpinan dan Disiplin Kerja Terdadap Kinerja Pegawai pada Bagian Manajemen di Rumah Sakit Umum Daerah Karawang - Skolastika Amanda Cinta Silence Hilgers; H. Budi Rismayadi; Wike Pertiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to analyze and examine how work discipline and leadership affect employee performance in the management department of Karawang Regional General Hospital. In this study, path analysis methods were used along with quantitative methodology to determine correlation, determination, and path coefficients. Researchers use f-test and t-test analysis to assess hypotheses. There are 45 samples in total, all of whom work in the management division. The following conclusions are drawn from the findings of the analysis: (1) Leadership (X1) and Work Discipline (X2) have a positive, moderate, and significant relationship, with a correlation value of 0.549. (2) With a path coefficient value of 0.854, there is no partial and significant influence of Leadership (X1) on Employee Performance (Y). (3) With a path coefficient value of 0.001, employee discipline (X2) has a partial and significant effect on employee performance (Y). (4) Results showed that work discipline (X2) and leadership (X1) had a significant and simultaneous influence on employee performance (Y), with the influence of 50.3% of both factors and the influence of 49.7% of other variables not included in this study.